Ethical Principles in Dental Research of Behavioral and Social Factors - Ramírez, Karol (2026)
Given the importance of conducting research ethically when studying humans, this article involves considerations on basic ethical principles in dental research of behavioral and social factors. Research in these fields contribute to understand social interactions, attitudes, individual and group dynamics. As well, research in these areas not only delve into scientific knowledge of human nature, but also support evidence-based decision-making of health policies and interventions. The four main ethical principles apply to studies on behavioral and social factors. First, respect for persons dictates researchers must protect participants’ autonomy, which is the basis for informed consent. Moreover, the principle of beneficence refers to act in such a way that participants benefit from taking part of a research study. Also, beneficence promotes participants’ safety and well-being. Non-maleficence requires that researchers avoid or minimize harm to others. Justice implies fair treatment. Additional aspects of justice involve respecting participants’ privacy and confidentiality. Ethical principles require interpretation. Therefore, some examples are provided, aiming that researchers overview and apply these norms. Ethical judgement and appropriate decision making are of great importance at any stage of research with human beings.